PENGARUH UKURAN PEMERINTAH DAERAH, TINGKAT KEKAYAAN DAERAH, TINGKAT KETERGANTUNGAN DAERAH KEPADA PEMERINTAH PUSAT DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH (Studi pada Kabupaten/Kota se-Provinsi Riau Periode 2011- 2016) - Alvini, Yevi; Basri, Yesi Mutia; Hasan, Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the effect of the size of local government, the level of regional wealth, the level of regional dependence to the central government and capital expenditure on the financial performance of local governments of Regency/City in Riau Province period 2011-2016. The population used in this study is the government of Regency/City in Riau Province, amounting to 12 Regency/City. The sampling technique in this research using purposive sampling method and based on predetermined criteria obtained the sample as much 11 Regency/City. This study uses secondary data in the form of financial data from LKPD of Regency / City in Riau Province in 2011-2016 obtained from the office of BPK RI Riau Province Representative. Hypothesis testing in this study using multiple linear regression analysis with t-test and coefficient determination test processed using SPSS 21. The results of this study indicate the size of local government affect the financial performance of local governments, the level of regional wealth affect the financial performance of local governments, the level of regional dependence to the central government does not affect the financial performance of local governments, capital expenditures affect the financial performance of local governments.Keywords : Size of Local Government, Level of Regional Wealth, Level of Region Dependence to Central Government, Capital Expenditure, Financial Performance of Local Government